STEREOTIP ISLAM DALAM SOUMISSION KARYA MICHEL HOULLEBECQ - Erwing, Erwing; Latjuba, Ade Yolanda; Hasbullah, Hasbullah (Universitas Hasanuddin, 2020)
The stereotype is a problem that we found when examining Michel Houllebecq's work entitled Soumission. As a form of prejudice against a particular ethnic / race or group, in this case, an Islamic group, this discourse is wrapped up in story elements. Therefore, to prove this thesis, this study is entitled